Pengembangan Instrumen Pembelajaran Fisika Berbasis Problem Based Learning untuk Meningkatkan Hasil Belajar Fisika Siswa SMA Negeri 1 Piyungan pada Materi Listrik Statis - Kawuri, Maria Yosephien Retna Tinon (Universitas Halu Oleo, 2021)
Problem-based learning is an alternative model offered in the K-13 curriculum. Therefore we need an instrument that supports and integrated with the problem-based learning model. This research aims to make a physics learning instrument based on problem-based learning to improve physics learning outcomes. This type of research classified as R & D (Research and Development) with a development design using 4-D (Four-D), which consists of defining, designing, developing, & disseminating. The material developed was static electricity; the research subjects consisted of class XII IPA1 SMA Negeri 1 Piyungan. The research instrument consisted of a questionnaire and learning outcome test questions with a field trial design using a pretest-posttest control group design. Meanwhile, the data analysis technique obtained from the assessment results of each validator based on the Aikent Value formula. The analysis results show that the physics learning instrument based on problem-based learning has met the requirements in the very good category. In learning outcomes, using physics learning instruments based on problem-based learning can improve student learning outcomes.